Novel Antihypertensive Drug Used in Clinical Practice: A Review: Novel Antihypertensive Drug Used in Clinical Practice: A Review - Bais, Dr. Sanjay (International Journal of Pharmaceutical & Biological Archive, 2020)
Introduction: Blood pressure (BP) control continues to be important in reducing cardiovascular risk, along with the modification of other cardiovascular risk factors, especially cholesterol level. Lifestyle modification to reduce BP may control Stage 1 hypertension. Drug treatment should be based on evidence of improved outcomes and individualized account for the patient age, race, and quality of life. BP varies from minute to minute and is influenced by measurement technique, time of day, emotion, pain, discomfort, hydration, temperature, exercise, posture, and drugs. Purpose of Review: In this review, we examine how synthetic novel drugs involved in the management of hypertension not only in the wider population but also within special population groups such as the elderly, pregnant women, and those with a trial fibrillation. Conclusion: The extensive synthetic work carried out shows that some molecules are very effectively managing the hypertension in all ages of patients. Summary: We have made an attempt in reviewing the literature on 1,2 pyrazoline derivatives for their medicinal uses with the help of chemical abstract, journals, and internet surfing.